Synthesis and Study of New Complexes of a Mixture of Liquandate for Schiff Bases Derived from Isatin and Amino Acids and Bi-Amine Liquandate with Iron Ion (II) - Khalaf Khaloo; Abeer Al Nuaimi (College of Education for Pure Sciences, 2013)
ABSTRACT The work includes the synthesis and characterization of new complexes of mixed ligands of Schiff  bases derived from isatin with amino acids (glycine,a-alanine,L-valine,L-leucine,L-histidine and L-tryptophane) (L¢) and diamine ligands(L²) with Fe(II) ion having the general formula[Fe(L¢)(L²)Cl(H2O)].nH2O; Where L²= bipyridyl(bpy) and 1,10-phenanthroline(phen) and n=0-8. These complexes were characterized by  many physicochemical methods such as molar conductance, elemental analysis(CHN)  for some of  them Fe(II) content using the atomic absorption spectroscopy and magnetic susceptibility measurement as well spectral studies such as IR and UV-Visible. The analytical data showed that the Schiff base ligands act as bidentate toward the Fe(II) ion via the azomethine nitrogen and carboxylate oxygen groups and through both nitrogen atoms of diamine ligands .The presence of chloride ion and aqua molecule gave the most probable octahedral geometry around the Fe(II) ion. The conductivity values imply the presence of non-electrolyte species as well, the magnetic measurements referred to the high spin character in all complexes.